Development of virgin polypropylene composite by sugarcane bagasse reinforcement - Nallappan, Madana Leela (2011)
This research is aimed to produce a high strength composite by reinforcement sugarcane bagasse as filler into virgin polypropylene. Bagasse fiber is a by-product of the sugar cane industry whose role is sugar or biofuel production. The bagasse filler is divided into two parent categories which are the pith and the rind. This study is focused on the determination of the optimum fibre content which gives maximum strength for each parent category and establishing which parent category gives optimum results with respect to strength. For each category extrusion was carried out at a temperature of 190oC and screw speed of 50 to 70rpm, for fibre content of 10 wt% to 50 wt%. The compounded samples were then prepared into test specimens through injection molding and characterized by tensile testing, Fourier Transform Infrared Spectroscopy (FTIR) and Melt Flow Index (MFI). Based on the tests, the fibre content that gives the maximum strength is identified. Comparisons are made and it is established that the rind gives better strength as filler, compared to the pith and that a 30 wt% fibre composition gives maximum strength.